The Nazi Bomb - Lindsay, Jim (History Channel, 1998)
Duration: 00:50:00 A fascinating look at the German A-bomb project, centering on the work of the Nobel Laureate physicist Werner Heisenberg. Did he deliberately mislead the Nazi leadership about the difficulties involved in building a bomb, or did he simply lose the race to more competent and committed scientists at Los Alamos? Documents and rare photos take us inside the top-secret Nazi program, while historians and scientists examine the many questionable decisions they made and question the reasons for them. The Germans had the money, the equipment, the natural resources and the scientists needed to develop the "ultimate weapon," yet they never completed the task. Why?